2019
DOI: 10.1017/s0022215119001944
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nasal foreign bodies in 341 children

Abstract: ObjectiveThis study aimed to analyse the common presentations and treatment outcomes in cases involving nasal foreign bodies.MethodsA retrospective study was carried out over three years, from January 2014 to December 2017. Patient biodata, clinical presentation, nasal foreign body type and management outcome data were obtained from the medical records and analysed.ResultsA total of 341 cases were analysed. The average patient age was 3.7 ± 1.2 years (range, 1–19 years).Of the nine cases involving button batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
1
13
3
Order By: Relevance
“…However, nosebleed was severe in cases of button battery impaction, and ulceration in the nasal mucosa might occur. Septal perforation due to button cell impaction was reported widely, [ 4 , 15 , 20 , 21 , 24 , 25 ] but no such complication occurred in our study. Only 5 of 20 children with button battery retraction went in for follow-ups.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…However, nosebleed was severe in cases of button battery impaction, and ulceration in the nasal mucosa might occur. Septal perforation due to button cell impaction was reported widely, [ 4 , 15 , 20 , 21 , 24 , 25 ] but no such complication occurred in our study. Only 5 of 20 children with button battery retraction went in for follow-ups.…”
Section: Discussioncontrasting
confidence: 43%
“…the local toxic effect due to the absorption of substances: this can be the case in mercuric oxide batteries. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nasal BB impaction occurs more frequently than esophageal and can cause septal necrosis and perforation, synechia, and long-term sequelae, such as saddle nose deformity. [1][2][3][4][5][6][7][8][9][10][11][12] Lou reported that septal perforation developed in seven of nine BB cases. They speculated that in the two other cases that did not develop septal perforation, weak acidic seawater spray had been used, and this neutralized the alkaline effect of the BBs.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that in the two other cases that did not develop septal perforation, weak acidic seawater spray had been used, and this neutralized the alkaline effect of the BBs. 10 Bakshi et al found that septal perforation developed in 11 cases with a mean follow-up of 11.6 months after removal that occurred after an average of 2 days. Diffuse bilateral changes were observed in two cases, unilateral adhesion in three, chronic maxillary sinusitis in three, atrophic changes in two, and saddle nose in one case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation